Parents’ Provision in Enhancing the Socialization Skills of Children with Sensory Disorders: A Descriptive Study - Campania, Venafe; Ubungen, Lendyrose T.; Samillano, Arcel A.; Quezada, Rodeth Jane C. (International Journal of Research in Interdisciplinary Studies, 2025)
The major factors in the socialization skills of children with sensory disorders often focus on the child's experience. However, a significant gap persists in understanding the dynamic interaction between sensory challenges and mothers' roles in providing support. This study is set to develop a deeper understanding of the techniques, practices, and strategies parents use to enhance the socialization skills of children with sensory disorders. Purposive sampling was used with six mothers of children with sensory disorders in Santa Cruz, Davao del Sur, aged 25-50, as participants. This study utilized a qualitative research design through in-depth interviews, specifically the phenomenological approach, through a validated questionnaire. It was found that proper communication and motivation techniques were the common factors that the mothers used to build up the socialization skills of their children. In addition, the results showed that improper communication was the challenge encountered by the mothers, and it further revealed that mothers deal with the challenges by providing an emotional support system, implementing coping strategies, and fostering positive self-worth.